Decentralization, Accountability and Local Services in Sierra Leone : Situation Analysis, Key Challenges and Opportunities for Reform - World Bank (Washington, DC, 2014)
Following years of civil war that ended in 2002, Sierra Leone has pursued a policy of decentralization, devolving responsibility for many government functions to the Local Council level. The aims of this policy include achieving a more equitable and inclusive access to public services across the national territory, in part to alleviate regional inequities that contributed to the civil war. The implementation of the decentralization policy has faced many obstacles, however, including the need to rebuild local government institutions and capacity after 30 years of centrally dominated governance; the limited devolution of financial resources; and multifaceted political economy hurdles. This report, first, analyzes the current state of decentralization in Sierra Leone; second, identifies the most prominent challenges to continued decentralization; and, third, discusses options for the way forward. The report draws on qualitative and quantitative data collected from both central and local government stakeholders, and takes the perspective that decentralization and strengthened local governance institutions are an effective means to localize development and improve the effective and equitable delivery of key public services. The study focuses on progress to date and standing challenges in four key areas of analysis: fiscal decentralization, human resource decentralization, ensuring inclusivity and accountability in local governance, and ensuring efficiency and responsiveness in service delivery.